2020
DOI: 10.23937/2378-3656/1410328
|View full text |Cite
|
Sign up to set email alerts
|

Can Coconut Oil Promote Non-Alcoholic Steatohepatitis and Metabolic Syndrome? A Timely Review

Abstract: Metabolic syndrome (MS) and non-alcoholic steatohepatitis (NASH) have been associated with bad eating habits. Supplementation with coconut oil (CO) has been proposed to control these conditions, as some authors suggest that CO provides weight loss and cardiovascular protective effects. However, the effectiveness and safety of emerging diets, such as CO, remain uncertain. This review focuses on the utilization of CO in the control of MS and NASH, besides in addition to describing this cardiovascular and weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…51 Moreover, an interesting study with high-fat diet-induced obesity in mice has revealed that CO enhanced the expression of thermogenesis markers in brown adipose tissue, which was consistent with the increased brown adipose tissue activity. 52 Finally, a recent review by Sanches et al 53 has shown a relationship among excessive CO consumption and consequences on metabolic syndrome and nonalcoholic steatohepatitis. This study agrees with the perspective that new clinical studies are necessary to verify the efficacy and safety of different doses of CO on hepatic and lipid metabolism.…”
Section: Discussionmentioning
confidence: 98%
“…51 Moreover, an interesting study with high-fat diet-induced obesity in mice has revealed that CO enhanced the expression of thermogenesis markers in brown adipose tissue, which was consistent with the increased brown adipose tissue activity. 52 Finally, a recent review by Sanches et al 53 has shown a relationship among excessive CO consumption and consequences on metabolic syndrome and nonalcoholic steatohepatitis. This study agrees with the perspective that new clinical studies are necessary to verify the efficacy and safety of different doses of CO on hepatic and lipid metabolism.…”
Section: Discussionmentioning
confidence: 98%